Macroeconomic Factors (Other Than The FIIs) Affecting the Sensex: An Empirical Analysis - Mohapatra, Siba Prasad; Panda, Brahmadev (Indian Journal of Finance, 2012)
This paper attempts to investigate the impact of various macroeconomic factors upon the movement of the stock market index, i.e. the BSE Sensex. The researchers opined that since liberalization, the FIIs have played a bigger role in the movement of the Indian stock market, but whether the FIIs are responsible for both the upward and the downward state of the Sensex remained to be seen. To get an answer to the posed question, the researchers made a correlation analysis between the top ten rises and the top ten falls of the Sensex with the corresponding net flow of FIIs to know exactly the dependency of the Sensex upon the FIIs. The results showed that FIIs have a higher correlation with the Sensex at the time of its downward spiral rather than upward growth. So here the question arises, can India stabilize the Sensex at the time of FII withdrawal by promoting any other factor? Thus, the researchers tested the impact of other macroeconomic factors along with FIIs affecting the Sensex for the last 10 years from March 2001 to April 2011. Correlation and multiple-regression models were used for this study and the results depict that IIP and Exchange Rate (INR/USD) have a higher influence (than FIIs) on the stock markets. The findings suggest that by improving the IIP figures and by controlling the Exchange Rate, the Sensex can be stabilized at the time of heavy selling by the FIIs in the Indian stock market.